Ten Influential Point-of-Care Ultrasound Papers: 2022 in Review. (June 2023) - Millington, Scott J.; Arntfield, Robert T.; Koenig, Seth J.; Mayo, Paul H.; Vieillard-Baron, Antoine
Keeping up with the latest developments in the point-of-care ultrasound (POCUS) literature is challenging, as with any area of medicine. Our group of POCUS experts has selected 10 influential papers from the past 12 months and provided a short summary of each. We hope to provide emergency physicians, intensivists, and other acute care providers with a succinct update concerning some key areas of ultrasound interest.